Dynamics of Upper Caste Paramountcy as Expressed in Dalit Literature A Reading of Sharankumar Limbales (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: dalit literature; untouchability; depressed classes; scheduled castes; resistance literature